Perilaku Berbahasa Indonesia Pendidik dan Pembelajar dalam Perspektif Globalisasi - Abdurahman . (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
This paper focuses on two phenomena, namely Indonesian language behavior and its perspectives in the globalization problems. Referring to the language behavior of Indonesian users, this paper discusses the behavior of the teachers and students in thinking, being, doing and acting in the perspective of globalization. In this regard the author has examined some of the problems faced by teachers and language learners based on experience and discussions with students and through reading the articles written by the observers of Indonesian language. The awareness on Indonesian language behaviors is needed to be actualized in a more contextual issue with creative solutions through interpretation and reinterpretation as well as the logical explanation, so that language behavior is more prospective in dealing with globalization. Keywords: language behavior, teacher-learner, globalization